Screening of Bangladeshi medicinal plants for their effects on pentobarbital-induced sleeping time in mice - CHAKMA, TK; KHAN, MTH; RAHMAN, T; CHOUDHURI, MSK; RAJIA, S; ALAMGIR, M (Ars Pharmaceutica (Internet), 2006)
Aqueous extracts of forty medicinal plants of Bangladesh have been screened for central nervous system activity bypentobarbital-induced sleeping time test. While twelve plants showed signifi cant increase in sleeping time, six plantsshowed signifi cant decrease. Woodfordia fruticosa and Uraria lagopodioides exhibited a better depressant effect thandiazepam.